1976
DOI: 10.1111/j.1751-0813.1976.tb05417.x
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Wild Animals in the Spread of Exotic Diseases in Australia

Abstract: The distributions of the following feral animals are given -- cattle, buffalo, pig, goat, deer, camel, horse, donkey, fox, dog and cat -- and the native dingo. The possible role these and the native rodents, marsupials and monotremes would play should an exotic disease of livestock enter Australia is discussed. It is considered that feral animals would be important in creating foci from which the disease would spread.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

1981
1981
2012
2012

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 18 publications
0
6
0
1
Order By: Relevance
“…This paper is one of a series, and reports the analysis of blood meals from some 11,000 insects, comprising some 7000 biting midges of 15 species and some 4000 mosquitoes of 24 species, to determine the mammalian hosts upon which they had fed. Particular attention was paid to the identification of blood meals from ox and buffalo, the latter being an abundant feral bovine in the area and potentially important as a reservoir host for both endemic and exotic diseases of livestock (Murray and Snowdon 1976).…”
Section: Introductionmentioning
confidence: 99%
“…This paper is one of a series, and reports the analysis of blood meals from some 11,000 insects, comprising some 7000 biting midges of 15 species and some 4000 mosquitoes of 24 species, to determine the mammalian hosts upon which they had fed. Particular attention was paid to the identification of blood meals from ox and buffalo, the latter being an abundant feral bovine in the area and potentially important as a reservoir host for both endemic and exotic diseases of livestock (Murray and Snowdon 1976).…”
Section: Introductionmentioning
confidence: 99%
“…In common with other feral animals they pose two distinct animal health problems. Feral goats may act as reservoirs for diseases already endemic in Australia and may serve as hosts for some exotic diseases should these be introduced, thereby establishing foci of infection not easily amenable to eradication or control (Murray and Snowdon 1976;Snowdon 1979).…”
Section: Introductionmentioning
confidence: 99%
“…West and Saunders (2003) found that the six deer species collectively inhabit 5% of NSW and the ACT, compared to 2% in an earlier survey in 1996. Even earlier reports by Wilson et al (1992) and Murray and Snowdon (1976) suggested that wild deer inhabited smaller areas of NSW than those observed in 1996. Despite this apparent increase in the size of the wild deer population, West and Saunders (2003) noted that in contrast to the many other introduced species in NSW, a majority of respondents to their survey did not perceive wild deer to be overly abundant.…”
Section: Introductionmentioning
confidence: 71%